Gene expression profiling of bone marrow mesenchymal stem cells from Osteogenesis Imperfecta patients during osteoblast differentiation - Kaneto, Carla Martins; Pereira Lima, Patrícia S.; Prata, Karen Lima; dos Santos, Jane Lima; de Pina Neto, João Monteiro; Panepucci, Rodrigo Alexandre; Noushmehr, Houtan; Covas, Dimas Tadeu; de Paula, Francisco José Alburquerque; Silva, Wilson Araújo (European journal of medical genetics, 2017)
Mesenchymal stem cells (MSCs) are precursors present in adult bone marrow that are able to differentiate into osteoblasts, adipocytes and chondroblasts that have gained great importance as a source for cell therapy. Recently, a number of studies involving the analysis of gene expression of undifferentiated MSCs and of MSCs in the differentiation into multiple lineage processes were observed but there is no information concerning the gene expression of MSCs from Osteogenesis Imperfecta (OI) patients. Osteogenesis Imperfecta is characterized as a genetic disorder in which a generalized osteopenia leads to excessive bone fragility and severe bone deformities. The aim of this study was to analyze gene expression profile during osteogenic differentiation from BMMSCs (Bone Marrow Mesenchymal Stem Cells) obtained from patients with Osteogenesis Imperfecta and from control subjects. Bone marrow samples were collected from three normal subjects and five patients with OI. Mononuclear cells were isolated for obtaining mesenchymal cells that had been expanded until osteogenic differentiation was induced. RNA was harvested at seven time points during the osteogenic differentiation period (D0, D+1, D+2, D+7, D+12, D+17 and D+21). Gene expression analysis was performed by the microarray technique and identified several differentially expressed genes. Some important genes for osteoblast differentiation had lower expression in OI patients, suggesting a smaller commitment of these patient's MSCs with the osteogenic lineage. Other genes also had their differential expression confirmed by RT-qPCR. An increase in the expression of genes related to adipocytes was observed, suggesting an increase of adipogenic differentiation at the expense osteogenic differentiation.